Do High Mental Demands at Work Protect Cognitive Health in Old Age via Hippocampal Volume? Results From a Community Sample - Rodriguez, Francisca S.; Huhn, Sebastian; Vega, William A.; Aranda, Maria P.; Schroeter, Matthias L.; Engel, Christoph; Baber, Ronny; Burkhardt, Ralph; Löffler, Markus; Thiery, Joachim; Villringer, Arno; Luck, Tobias; et al. (Frontiers in Aging Neuroscience, 2021)
As higher mental demands at work are associated with a lower dementia risk and a key symptom of dementia is hippocampal atrophy, the study aimed at investigating the association between mental demands at work and hippocampal volume. We analyzed data from the population-based LIFE-Adult-Study in Leipzig, Germany (n=1,409, age 40 to 80). Hippocampal volumes was measured via three-dimensional Magnetic Resonance Imaging (3D MP-RAGE) and mental demands at work were classified via the O*NET database. Linear regression analyses adjusted for gender, age, education, APOE e4-allele, hypertension, and diabetes revealed associations between higher demands in ‘language & knowledge’, ‘information processing’, and ‘creativity’ at work on larger white and gray matter volume and better cognitive functioning with ‘creativity’ having stronger effects for people not yet retired. Among retired individuals, higher demands in ‘pattern detection’ were associated with larger white matter volume as well as larger hippocampal subfields CA2 / CA3, suggesting a retention effect later in life. There were no other relevant associations with hippocampal volume. Our findings do not support the idea that mental demands at work protect cognitive health via hippocampal volume or via brain volume. Further research may clarify through what mechanism mentally demanding activities influence specifically dementia pathology in the brain.